Acute Effects of Salvia Supplementation on Cognitive Function in Athletes During a Fatiguing Cycling Exercise: A Randomized Cross-Over, Placebo-Controlled, and Double-Blind Study - Babault, Nicolas; Noureddine, Ahmad; Amiez, Nicolas; Guillemet, Damien; Cometti, Carole (Frontiers in Nutrition, 2021)
Background: Salvia (sage) supplementation has been shown to improve the cognition function in healthy individuals or patients (e.g., attention, memory). To date, no study has explored its relevancy in the context of sporting performance. The aim of the present study was to explore the acute effects of a combination of Salvia officinalis and Salvia lavandulaefolia on cognitive function in athletes performing a fatiguing cycling task. Methods: Twenty-six volunteers were included in this cross-over, randomized, double-bind vs. placebo trial. Two hours before the two experimental sessions (here called SAGE and PLACEBO), volunteers randomly received a supplementation of sage or placebo. During each experimental session, participants were tested at four occasions while cycling during a warm-up, in the middle and at the end of a fatiguing task and after a short 5-minutes recovery. Tests included a Stroop task, a simple reaction time task and a backward digit span memory task. Heart rate and rating of perceived exertion (RPE) were also measured at the beginning of the four test sessions. Results: Heart rate was significantly greater during the fatiguing exercise than during warm-up and recovery (P < 0.001) without any supplementation effect. RPE was greater during the fatiguing exercise than during warm-up and recovery (P < 0.001). Moreover, RPE was significantly lower during the SAGE session as compared to PLACEBO (P = 0.002). Reaction time was not altered during the exercise but was significantly shorter with SAGE as compared to PLACEBO (P = 0.023). The Stroop task only revealed significantly longer reaction time during warm-up as compared to recovery (P = 0.02) independently of the supplementation. The digit span memory test revealed a significant greater span score with SAGE as compared to PLACEBO (P = 0.044). Conclusion: The combination of Salvia improved the cognitive function (perceived exertion, working memory and reaction time). The positive effects were obtained in fresh condition and were maintained with fatigue.